2009
DOI: 10.1007/s10763-009-9153-3
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge Transfer in Biology and Translation Across External Representations: Experts' Views and Challenges for Learning

Abstract: ABSTRACT. Recent curriculum reform promotes core competencies such as desired 'content knowledge' and 'communication' for meaningful learning in biology. Understanding in biology is demonstrated when pupils can apply acquired knowledge to new tasks. This process requires the transfer of knowledge and the subordinate process of translation across external representations. This study sought ten experts' views on the role of transfer and translation processes in biology learning. Qualitative analysis of the respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 24 publications
3
38
0
1
Order By: Relevance
“…After the laboratory experiment, the obtained results show that the indigenous knowledge is scientifically proved and is now used by modern society as the product of technology. The experimental results are in accordance with the opinion of Cimer (2007); Schonborn & Bogeholz (2009). They stated that the indigenous knowledge of local communities has the scientific secret that can be verified through the application of scientific methods.…”
Section: Statement Average Categorysupporting
confidence: 86%
“…After the laboratory experiment, the obtained results show that the indigenous knowledge is scientifically proved and is now used by modern society as the product of technology. The experimental results are in accordance with the opinion of Cimer (2007); Schonborn & Bogeholz (2009). They stated that the indigenous knowledge of local communities has the scientific secret that can be verified through the application of scientific methods.…”
Section: Statement Average Categorysupporting
confidence: 86%
“…To develop an integrated understanding of this concept, students would need to ''move'' or translate across these different ERs, including decoding the different symbolism in each ER and linking the relationships between each ER [46]. Schö nborn and Bö geholz [30] have built on the idea of translation in a biology context by defining a horizontal translation, which deals with interpreting ERs that represent a phenomenon at the same level of biological organization, whether it be at the macro-, micro-or molecular level. Qu.…”
Section: Translate Horizontally Across Multiple Ers Of a Conceptmentioning
confidence: 99%
“…All biochemists require the skills to translate vertically ''between'' levels of biological organization and complexity [30]. For example, in the case of a biological tissue, it might be necessary to translate between ERs that represent the visible and tangible macro-level, the microscopic level, as well as the molecular level of biological organization [35].…”
Section: Translate Vertically Between Ers That Depict Different Levelmentioning
confidence: 99%
See 1 more Smart Citation
“…In conclusion, although biology education research has shown that knowledge transfer is often a demanding process for learners to engage in [40], it is perhaps the most essential expert facet of conceptual understanding in biochemistry and molecular biology and it should be explicitly developed and assessed in our students.…”
Section: Transfer and Apply Knowledge Of The Concept Tomentioning
confidence: 99%